Effect of integrating traditional and modern healthcare systems on tuberculosis case detection in Ethiopia: a cluster randomized controlled study - Desalegne Amare; Kefyalew Addis Alene; Fentie Ambaw (Infectious Diseases of Poverty)
Abstract Background Low tuberculosis (TB) case detection remains a major challenge in achieving the End TB targets. New strategies that consider local contexts are needed in countries with high TB burdens like Ethiopia. This study examined the effect of integrating traditional and modern TB care to increase the TB case detection rate. Methods A cluster randomized controlled trial was conducted from February 2023 to January 2024 in six districts of South Gondar Zone, Northwest Ethiopia, where districts were randomly assigned to intervention or control groups. The interventions included training, screening, and referral of presumptive TB patients, delivered over one year, while the control group continued with the standard passive case detection approach. A paired t-test and two sample independent t-test were used to compare baseline and end line data for both groups. Cohen's d was also used to compare the effect size between the intervention and the control groups. A mixed-effect Poisson regression was employed to determine the association between the dependent variable and the exposure variables. Results In the intervention group, a total of 620 TB cases were identified post-intervention, compared with 473 cases pre-intervention, including 14 cases identified through referrals by traditional care providers. In contrast, the control group identified 298 TB cases post-intervention and 279 pre-intervention. The TB detection rate increased to 93 cases per 100,000 population in the intervention group, making an approximate 29.2% improvement, compared to a 2.9% increase in the control group. Integrating traditional care with the modern healthcare system significantly increased case detection, with a standardized mean difference of 2.6 (95% confidence interval CI: (1.8, 3.5; t = 8.3; P < 0.001) in a two-sample independent t-test. Conclusions Integrating traditional care with the modern healthcare system significantly increased TB case detection in high-burden settings. This approach not only enhances current TB control strategies but also has potential applications in managing other chronic diseases in resource-limited areas. Future research should evaluate the cost-effectiveness, scalability, and sustainability of this integrative model. Trial registration Unique Protocol ID: 353/2021. ClinicalTrials.gov ID: NCT05236452. The date recruitment began: July 1, 2022. Registration date: July 22, 2022.